PENGARUH GOVERNANCE STRUCTURE DAN FUNGSI INTERNAL CONTROL TERHADAP FEE AUDIT EKSTERNAL PADA PERUSAHAAN PUBLIK DI INDONESIA - Reza Wibowo; Abdul Rohman (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine the influence of the characteristics of governance structure (board of commissioners, audit committee, and concentration of ownership) and internal control function on external audit fees. The existence of the board of commissioners, audit committee, and concentration of ownership as a mechanism of checks and balance and internal control function as a internal control mechanism is expected to reduce control risk, so that lower external audit fees can be achieved. This study uses secondary data from financial statements and annual reports of manufacturing companies which listed on Bursa Efek Indonesia in 2009-2011. This study uses purposive sampling method and uses multiple linier regression as the analysis instrument. Before being conducted the regression test, it is examined by using the classical assumption test. The result of this study indicate that the independence board of commissioners, the independence audit committee, the meeting intensity of audit committee, and the internal audit function did not influence the external audit fees. The meeting intensity of the board of commissioners and the concentration of ownership have significant positive relationship on the external audit fees. It means that the board of commissioners who held frequent meetings and the existence of concentrated ownership will demand a high quality audit from external auditors, resulting in higher audit fees. While the size of board of commissioners and the size of audit committee have significant negative relationship on the external audit fees. It means that board of commissioners that are small, will be more effective in checks and balances the financial reporting, and will be more support the external audit function, so that there is will increase audit scope activity, that will increase audit fees. While the audit committee that ara large will increase the quality of financial reporting which leads to lower external audit fees.